2021
DOI: 10.1177/0267658321992461
|View full text |Cite
|
Sign up to set email alerts
|

The effects of information structure in the processing of word order variation in the second language

Abstract: Traditionally, it has been claimed that the non-canonical word order of passives makes them inherently more difficult to comprehend than their canonical active counterparts both in the first (L1) and second language (L2). However, growing evidence suggests that non-canonical word orders are not inherently more difficult to process than canonical counterparts when presented with discourse contexts that license their information structure constraints. In an eye-tracking experiment, we investigated the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 137 publications
0
9
0
Order By: Relevance
“…In order to implement the aim and tasks, the following methods were used: theoretical analysis of psychological and pedagogical, sociological, linguistic literature on the research problem; a study of the survey bilinguals (children and adults) in Russia and abroad [1][2][3][4][5][6][7][8][9][10][11][12][13][14]; questionnaires, testing, surveys of bilingual students studying at Moscow universities and St. Petersburg universities; analysis of expert opinions and procedures for assessing the quality of education in groups; analysis of statistical data. The diagnostic measures are based on projective research methods: the method of semantic differential [15], which allows determining the emotional attitude of the subjects to the manifestations of language attrition; the method of unfinished sentences (MUS), which provided material for analyzing the status characteristics of languages in the minds of bilingual speakers.…”
Section: Methodsmentioning
confidence: 99%
“…In order to implement the aim and tasks, the following methods were used: theoretical analysis of psychological and pedagogical, sociological, linguistic literature on the research problem; a study of the survey bilinguals (children and adults) in Russia and abroad [1][2][3][4][5][6][7][8][9][10][11][12][13][14]; questionnaires, testing, surveys of bilingual students studying at Moscow universities and St. Petersburg universities; analysis of expert opinions and procedures for assessing the quality of education in groups; analysis of statistical data. The diagnostic measures are based on projective research methods: the method of semantic differential [15], which allows determining the emotional attitude of the subjects to the manifestations of language attrition; the method of unfinished sentences (MUS), which provided material for analyzing the status characteristics of languages in the minds of bilingual speakers.…”
Section: Methodsmentioning
confidence: 99%
“…While previous studies have reported varying findings regarding L2 acquisition of the linguistic properties at the syntax–discourse interface, most evidence comes from offline judgment or production tasks, rendering it difficult to draw firm conclusions about whether L2 learners are able to use this knowledge during online processing. A recent study by López-Beltrán et al (2022) addressed this issue in part by investigating Spanish-speaking learners’ processing of English active and passive sentences under different contexts. Based on the well-known discourse constraint on passives that a referent represented as given information is more likely to occupy the subject position in a passive sentence, López-Beltrán et al (2022) used a self-paced reading task to examine whether L2 learners would show sensitivity to this constraint during online processing.…”
Section: L2 Processing Of Syntax–discourse Interactionmentioning
confidence: 99%
“…A recent study by López-Beltrán et al (2022) addressed this issue in part by investigating Spanish-speaking learners’ processing of English active and passive sentences under different contexts. Based on the well-known discourse constraint on passives that a referent represented as given information is more likely to occupy the subject position in a passive sentence, López-Beltrán et al (2022) used a self-paced reading task to examine whether L2 learners would show sensitivity to this constraint during online processing. Their results showed that L2 learners’ reading speed in passive sentences significantly slowed when the subject referent was newly introduced in the target sentence (new theme subject condition) compared to when the subject referent had been mentioned in a prior context (given theme subject condition).…”
Section: L2 Processing Of Syntax–discourse Interactionmentioning
confidence: 99%
See 2 more Smart Citations